Multi-cluster and environmental dependant vector born disease models. Issue 9 (September 2020) - Vyhmeister, Eduardo; Provan, Gregory; Doyle, Blaine; Bourke, Brian
Abstract: Vector-born disease models are extensively used for surveillance and control processes. The most simple and generally use model (SEIR-SEI model) cannot explain a variety of phenomena involved in these diseases spread and development. In order to obtain a wider insight of the vector-born disease models (and the dynamics involved in them), this work focuses into analyse the classical model, a modified versions of it, and 8 their parameters. The modified version includes host mobility, 9 environmental, re-susceptibility, and mosquito life cycle considerations. As results it is observed that there are a limiting number of parameters that play the most important roles in the dynamics (those related to mortality rates, recovery rate from infectious, and pathogen transmission probabilities). Therefore, parameters determination should focus primarily into estimate these values. Stronger effects of the environmental variables are observed and expected by using different parameters and/or the use of multiple environmental variable at the same time. Abstract : Applied Mathematics; Engineering; Computer-Aided Engineering; Ecology; Biological Sciences; Epidemiology; modelling; Vector-Borne Diseases; SEIR-SEI; dengue; Clustering; Sensitivity Analyses